Figurative Language in Song Lyric “Red” by Taylor Swift - Dianti Rini Rahmani; Sukma Septian Nasution (Universitas Pamulang, 2019)
Observing the figurative language in a song lyric entitled “Red” by Taylor Swift, this study aims at (1) finding out kinds of figurative language and (2) analyzing the appropriate intent of figurative language Taylor Swift’s song. This study uses a song from the fourth Taylor Swift's album called Red. This study employs qualitative methods in data collection. After collecting the data, it encompasses that simile and hyperbole are dominantly found. It also reveals that figurative language used in this song is to deliver her deepest feeling. The use of figurative language in this song is very dominant which can provide knowledge to the reader to know the type of figurative language.